Rates of skincare product and cosmetic procedure use in patients with acne vulgaris and the effective factors: A multicenter study with 1,755 patients - Kayiran, Melek Aslan; Karadag, Aye Serap; Alyamac, Gokcen; Cemil, Bengu Cevirgen; Demirseren, Duriye Deniz; Demircan, Yuhanize Tas; Alpsoy, Erkan (Wiley, 2022)
Background Skincare products and cosmetic procedures are used as an adjunct or complementary to conventional drug therapy for acne vulgaris (AV). Objective To evaluate the use of skincare products and the frequency of cosmetic procedures in AV treatment. Methods A total of 1,755 patients with AV completed the survey prepared by the researchers and the Cardiff Acne Disability Index (CADI) questionnaire. The clinical findings and the Food and Drug Administration (FDA) severity scores were recorded by the dermatologists. Results For AV, 66.7% of the patients stated that they used skincare products and 26.7% had undergone cosmetic procedures. The use of skincare products was statistically significantly higher in women (female: 74.5%, male: 57.7%, p < 0.0001); older people (users: 22 +/- 7.6years, non-users: 21.2 +/- 5.7 years, p < 0.0001); patients with a higher CADI score (users: 7 +/- 3.7, non-users: 6.9 +/- 4.3, p = 0.010); FDA severity score 2 and 3 (FDA-1: 58.1%; FDA-2: 72.4%, FDA-3: 73%, FDA-4: 67%, p < 0.0001); long-term disease (users: 57 +/- 43 months; non-users: 47.7 +/- 42.3 months, p < 0.0001); facial involvement (present: 70.2%, absent: 51.4%, p = 0.017); high income levels (users: 73.5%; non-users: 26.5%, p = 0.001); and graduate or post-graduate degrees (undergraduate <=%62.8, graduate >=%76.8, p < 0.0001). The rate of cosmetic procedures was higher in those with higher CADI scores (users: 7.8 +/- 3.8; non-users: 7.1 +/- 3.96, p < 0.0001); older patients (users: 22.7 +/- 10.7 years; non-users: 21.3 +/- 5 years, p < 0.0001); high school (25.6%); and graduate (28.9%) education (p = 0.043), those with lower disease severity (FDA-1: 31.1%; FDA-2: 28.5%, FDA-3: 27.1%, FDA-4: 20.4%, p = 0.022); smokers (smokers: 32.5%; non-smokers: 25.5%, p = 0.020), and those with AV in the family (present: 29.8%; absent: 24.2%, p = 0.009). The patients most frequently used cleansers (85.2%) as cosmetic products, and most commonly underwent skincare treatment (71%) as an interventional procedure. They mostly learned about such products and methods from the Internet, and 33.3% of the participants had undergone procedures performed by non-physicians. Conclusion The patients generally choose skincare products as a result of their Internet search and sometimes have these procedures performed by non-physicians. Dermatologists should be aware of this situation and inform their patients about appropriate products and procedures.
Keywords: acne vulgaris; cosmetic procedure; skincare product